Chingoma Precinct: a creative hub unleashing digital potential in Mbare; "an urban regeneration project'' - Jambwa, Rufaro (My University, 2021)
Social media sites such as YouTube, Facebook and Instagram have given young people in Zimbabwe a platform to share their creativity and political ingenuity. The digital age has made it easier for individuals to release content that reaches a wide local and diaspora audience. Social media platforms have economically uplifted individuals involved, as they have a wider reach both in terms of clientele and markets. The most successful social media personalities have managed to penetrate the enormous high-density suburbs market mainly made up of unemployed youths. The design proposal aims to connect architectural space in the high-density suburbs with the new digital platforms that have become a source of income and livelihood. Since Mbare is home to most of the legends and upcoming artists in music, sculptural arts, and drama, it has been chosen as a place to build “Chingoma Precinct”, a creative hub. The hub seeks to promote young people eager to work in front and behind the camera as well as another art medium. Although Mbare stands in its dire urban condition and has been embraced in its rich cultural influence from the practice of Nyau Society (Gule Wamukulu), elements of Jit music and a new era of Zimbabwean dancehall. Young people brought up in such an environment have found a calling in the Arts. It is fair to create a formal space that inspires and technically equips and refines. Their craft. Investing in young talent has indicated growth economically because social media remunerates for more viewership
This document is submitted in partial fulfilment for the degree of Master of Architecture [Professional], Faculty of Engineering and the Built Environment, University of the Witwatersrand, 2021.